Bottom-up synthesis of 2D layered high-entropy transition metal hydroxides. Issue 11 (13th May 2022) - Li, Fei; Sun, Shi-Kuan; Chen, Yinjuan; Naka, Takashi; Hashishin, Takeshi; Maruyama, Jun; Abe, Hiroya
Abstract : A facile polyol process is presented to synthesize equimolar high-entropy metal hydroxides with 2D layered structures for the oxygen evolution reaction. Abstract : Low-dimensional high-entropy materials, such as nanoparticles and two-dimensional (2D) layers, have great potential for catalysis and energy applications. However, it is still challenging to synthesize 2D layered high-entropy materials through a bottom-up soft chemistry method, due to the difficulty of mixing and assembling multiple elements in 2D layers. Here, we report a simple polyol process for the synthesis of a series of 2D layered high-entropy transition metal (Co, Cr, Fe, Mn, Ni, and Zn) hydroxides (HEHs), involving the hydrolysis and inorganic polymerization of metal-containing species in ethylene glycol media. The as-synthesized HEHs demonstrate 2D layered structures with interlayer distances ranging from 0.860 to 0.987 nm and homogeneous elemental distribution of designed equimolar stoichiometry in the layers. These 2D HEHs exhibit a low overpotential of 275 mV at 10 mA cm −2 in a 0.1 M KOH electrolyte for the oxygen evolution reaction. Superparamagnetic spinel-type high-entropy nanoparticles can also be obtained by annealing these HEHs. Our polyol approach creates opportunities for synthesizing low-dimensional high-entropy materials with promising properties and applications.